Adult Outcome of ADHD: An Overview of Results From the MGH Longitudinal Family Studies of Pediatrically and Psychiatrically Referred Youth With and Without ADHD of Both Sexes. Issue 6 (April 2018) - Uchida, Mai; Spencer, Thomas J.; Faraone, Stephen V.; Biederman, Joseph
Objective: We aimed to provide an overview of the Massachusetts General Hospital (MGH) Longitudinal Studies of ADHD.Methods: We evaluated and followed samples of boys and girls with and without ADHD ascertained from psychiatric and pediatric sources and their families.Results: These studies documented that ADHD in both sexes is associated with high levels of persistence into adulthood, high levels of familiality with ADHD and other psychiatric disorders, a wide range of comorbid psychiatric and cognitive disorders including mood, anxiety, and substance use disorders, learning disabilities, executive function deficits, emotional dysregulation, and autistic traits as well as functional impairments. The MGH studies suggested that stimulant treatment decreased risks of developing comorbid psychiatric disorders, substance use disorders, and functional outcomes. The MGH studies documented the neural basis of persistence of ADHD using neuroimaging.Conclusion: The MGH studies provided various insights on symptoms, course, functions, comorbidities, and neuroscience of ADHD.